Breakfast-Based Dietary Patterns and Obesity in Tehranian Adults - Akbarzade, Zahra (J Obes Metab Syndr, 2020)
BACKGROUND: Breakfast is an important meal of the day that contributes to an overall healthy dietary pattern, better nutrient intake, and diet quality. This study sought to investigate the relationship between breakfast patterns and general and central obesity among middle-aged adults. METHODS: In this cross-sectional study of 840 apparently healthy women and men, aged 20?59 years, we assessed usual dietary intake by means of three 24-hour dietary recalls and we took anthropometric measurements. Dietary patterns were subsequently identified by factor analysis. To assess the association between breakfast composition and central and general obesity, logistic regression analysis was performed. RESULTS: We identified three major dietary patterns by factor analysis: the “bread and grains, meat products, and coffee” dietary pattern, the “sweets, tea and coffee” dietary pattern, and the “fruits, vegetables, and eggs” dietary pattern. Those people in the third tertile of the “sweets, tea and coffee” dietary category had a greater chance of having central obesity (odds ratio, 1.80; 95% confidence interval, 1.25?2.59; P=0.001). Moreover, higher adherence to the “bread and grains, meat products, and coffee” pattern increased the chance of central obesity (odds ratio, 1.67; 95% confidence interval, 1.47?1.97; P=0.03). CONCLUSION: Overall, our results suggest that specific breakfast dietary patterns are associated with increased odds of central obesity in Iranian adults.